PENGARUH PENGHINDARAN PAJAK DAN BIAYA AGENSI TERHADAP NILAI PERUSAHAAN - Enggar Adityamurti; Imam Ghozali (Diponegoro Journal of Accounting, 2017)
This study aims to test the effect of tax avoidance as independent variable, agency cost and firm value as dependent variable.Type of data used in this study is secondary data. The population of the study is all manufacture companies listed in Indonesia Stock Exchange. To collect the sample, the writer employed purposive sampling method and applied criteria listed in Indonesia Stock Exchange, reported annually subsequently from 2013-2015. There was tax avoidance, agency cost, and firm value in financial report.The result of this study shows that tax avoidance not influenced the firm value. Meanwhile, tax avoidance effectiveness significantly influenced agency cost. In other side, agency cost significantly firm value in manufacture companies in Indonesia from 2013-2015.